EFFECT OF PARTIAL PURIFIED LOVASTATIN FROM ASPERGILLUS TERREUS A50 ON LIPID PROFILE AND LIVER ENZYMES IN VIVO - Al-Sa’ady, A.J.; Aziz, G. M.; Al-Obaidi, M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was designed to determine the effect of partial purified lovastatin on the lipid profile and liver functions in rabbits. The rabbits were divided into six groups, each group containing four rabbits, and the lipid profile and liver functions were checked at zero, 30, 60, and 90 days. The parameters of the cholesterol, high-density lipoprotein (HDL), triglycerides (TG), low-density lipoprotein (LDL), very- low-density lipoprotein (VLDL), blood bilirubin (BB), and liver enzymes (ALP, ALT and AST) were determined separately. Determination of parameters was made before treatment with any medication and after treatment with cholesterol (4 g/kilo/day), standard lovastatin (0.4 mg/kilo/day), cholesterol plus standard lovastatin 4g+0.4mg/kilo/day), partial purified lovastatin (0.4 mg/kilo/day), and cholesterol plus partial purified lovastatin (4g+0.4mg/kilo/day). The findings showed that partial purified lovastatin have influence on lipid profile and liver function with significant differences (positive effect) (P≤0.05) in the mean of cholesterol, TG, HDL-C, LDL-C, VLDL-C, ALP, ALT, AST and BB levels in compression with the control group, but some of them were higher than the normal value. In addition no significant differences (P≥0.05) in lipid profile and liver function enzymes activity if treatment with standard or partially purified lovastatin.